Horn and coat color varieties of the Hungarian grey cattle - Radácsi, Andrea; Bodó, Imre; Béri, Béla (Acta Agraria Debreceniensis, 2006)
Due to the intensification of agricultural production, genetic diversity has been reduced to a large extent. Presently, in the period of worldwide genetic conservation, we try to preserve as much of the gene pool of our valuable indigenous domestic animal breeds as we can. Therefore, traits that have no economic value at the moment should also be conserved. The different horn and coat colour varieties of Hungarian Grey Cattle are such valuable traits. Research has been done on the largest Hungarian Grey Cattle stock, at the Hortobágy Kht. Rates of the different horn and coat colour varieties were determined and relationships were analyzed between the above mentioned qualitative traits